Distance education, independent work and responsibility of medical students in times of COVID-19 - Dunia Chávez Amaro; Jorge Luis Capote Padrón (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2020)
In today's university context, independent work exerts an important influence on the formation of values in medical students. It is appropriate to highlight that, in emergency situations such as the COVID-19 pandemic, it is evident that an adequate implementation of independent work, as an organizational form of teaching work, develops cognitive independence and reinforces the value of responsibility in university students. In this article the authors detail the way in which, in the Distance Education modality, the responsibility value can be reinforced, from the curricular point of view, with correct planning, orientation, execution and control of independent work.